Quantitative assessment of the reproductive potential of women of early fertile age (Environment & Health, 2019)
Nowadays the strengthening of the preventive direction and the orientation on the health-saving strategy of the healthcare sector becomes especially relevant. The assessment of the reproductive health quality is a complex process as it involves a quantitative generalization of the interrelations of many factors that have different measurement units and ranges of changes. The article deals with a possibility of the use of the quantitative and qualitative parameters which characterize the reproductive potential of the women in general.Objective: We developed a method for the quantitative assessment of the reproductive potential of the women of early fertile age.Material and methods: 284 female students of Sumy higher schools took part in the research. They aged 17 - 22 years (I group (145 people) and 20 - 22 years (II group (139 people). We applied the methods of expert evaluation with a definition of the weight coefficients on the basis of the pair comparisons after T. Saati, anthropometric and psychological examination, subjective assessment of health competence, copying of the data on the presence/absence of the extra-genital pathology from medical records, state of reproductive health.Results and discussion: According to the totality and significance of the experts’ answers, the reproductive potential of the girls is determined mostly by the factors of the “presence/absence of hereditary diseases in the family” and the “health competence” (by the subjective assessment of the reproductive health awareness). The individuals with an average level of integrated assessment of the reproductive potential prevailed among girls, and with an age, the proportion of the female students with a high level of the studied parameter tends to increase.The high level of the reproductive potential of the girls depends on the propensity to a feminine type of gender identity, the level of motivation to achieve career success, the mature reproductive behavior (a responsible attitude towards oneself and a partner in the intimate relationships).Conclusions: The factors, affecting the formation of the reproductive potential of the women of early fertile age, can be estimated by the assigning of the appropriate weight coefficients to them, the analysis of these coefficients may allow identifying the prior measures to reduce their negative impact on the research object.
Keywords: reproductive potential; expert evaluation; fertile age; weight coefficients